PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Melviona "; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Family Hope Program (PKH) is one of the Conditional Cash Transfer (BTB) programs to accelerate poverty reduction. Which is the hope family program itself is trying to do poverty eradication. The Family Hope Program is a social protection program that provides cash assistance to the Very Poor Household (RTSM) and for family members is required to enforce the general terms and conditions set forth in the field of education and health.The implementation of Family Hope Program in BatangPeranapSubdistrict has been running since last three years. The problem of the researcher is to know how the implementation of Family Hope Program (PKH) in BatangPeranapSubdistrict of Indragiri Hulu Regency and what are the constraining factors in the implementation of Family Hope Program (PKH) in BatangPeranapSubdistrict Indragiri Hulu Regency.The concept of the theory used is the management theory propounded by G. R. Terrry in Manullangthat consisting of planning, organizing, directing, and controlling. This study used descriptive qualitative research. Data collected through observation, interviews, and documentation.The results of this study indicate that the implementation of Family Hope Program (PKH) in BatangPeranapSubdistrict Indragiri Hulu Regency is not fully optimal and there are still many obstacles that occur. Then the inhibiting factors in the implementation of Family Hope Program (PKH) is the participation, facilities and infrastructure.Keywords: Implementation, Family Hope Program.